The Effects of Blended Learning on the Performance of Engineering Students in Mathematical Modeling - Luis Javier López-Reyes; Auria Lucia Jiménez-Gutiérrez; Diana Costilla-López (MDPI AG, 2022)
This paper presents the implementation of an active learning methodology known as blended learning in an ordinary differential equations (ODE) course for engineering students. Our purpose was to evaluate the effect of b-learning on students' mathematical modeling performance. To this end, synchronous and asynchronous activities were made available to the students as face-to-face and remote learning sessions, in which the experience acquired by students during the sanitary isolation due to COVID-19 was crucial. Benjamin Bloom's cognitive domain taxonomy was used to design the present didactic proposal. Results show that the students moved upward from the lower knowledge and understanding taxonomical levels, to the upper analysis and application levels, as they learned systems modeling using ODEs.